MENEMUKAN PERPADUAN E-GOVERNANCE SEKULER DAN NILAI ISLAMI DEMI KEMASLAHATAN PUBLIK INDONESIA - Yusuf, Muhammad Rizaldy (Universitas Al-Amien Prenduan, 2024)
AbstractThis research aims to explain that in the discourse of the discipline area of public administration and public policy, the combination of information technology developments in the form of E-Governance can be combined with Islamic values and provide a reference from the best practices of E-Governance in the world today. This research was prepared using a qualitative descriptive approach. The result of this research is the fact that Islamic values can be combined with secular Estonian-style E-Governance without conflict. This begins by explaining the Estonian E-Governance as a benchmark position of Islamic values in E-Governance, and descripting opportunities for integrating E-Governance in Indonesia in the future.